PENGARUH KEPEMILIKAN MANAJERIAL DAN MANAGERIAL ABILITY TERHADAP PENGHINDARAN PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI PEMODERASI - Syifa Saida Rahma (2023)
This study was conducted to examine the effect of managerial ownership and managerial ability on tax avoidance with firm size as moderating variable and profitability and leverage as control variables. This study is a quantitative research using fixed effect model. This study uses secondary data in the form of company annual reports. The sampling technique used purposive sampling with a total of 261 samples from 87 manufacturing companies in 2019-2021. The results of data analysis indicate that (1) managerial ownership has no effect on tax avoidance, (2) managerial ability has a significant negative effect on tax avoidance, (3) firm size has no effect in strengthening the relationship between managerial ownership and tax avoidance, and (4) firm size has no effect in strengthening the relationship between managerial ability and tax avoidance.